Advances in ureteral stents - Brotherhood, Hilary; Lange, Dirk; Chew, Ben H. (Translational Andrology and Urology, 2014)
Ureteral stents are commonly used in urology. Every urologist is familiar with the problems that are associated with stents including infection, encrustation, and bothersome symptoms. These problems limit and affect the use of ureteral stents which are necessary, even in light of the problems they can cause. New designs such as a helically cut ureteral stent which is designed to stretch and conform to the ureter is designed to improve comfort. Drug-eluting designs with an antimicrobial (triclosan) are designed to reduce bacterial adherence to ureteral stents. Chlorhexidine, an antiseptic, has been incorporated into a stent and held in place by a slow release varnish to prevent biofilm formation. Combinations of antibiotics coated directly on the stent and administered systemically have been shown to reduce stent colonization both in vitro and in vivo. Gel-based ureteral stents were also showed to reduce bacterial infection and colonization. Bioabsorbable materials have also been designed to reduce infection, symptoms and prevent the forgotten stent syndrome. Newer designs including stents based on guidewire technology, gels, and a combination of self-expanding wire stents with polymer films are reviewed. There is hope on the horizon that new stents will be able to effectively tackle problems that are often seen with ureteral stents.